A CASE OF THE LEFT ATRIUM APPENDAGE OCCLUSION, SUGGESTIONS ON THE CLINICAL FIELD DEVELOPMENT - K. V. Davtian; A. A. Kalemberg; G. Yu. Simonian; V. S. Shatakhtsian; A. G. Topchian (Российский кардиологический журнал, 2017)
Aim. To evaluate the possibility of hybrid procedure that includes single-moment cryoballoon isolation of pulmonary veins (PV) ostia and implantation of occluder into the left atrium appendage (LAA) in patients of high thromboembolic and hemorrhagic risk and prominent symptoms in atrial fibrillation (AF) paroxysms.Material and methods. From 2012 to 2016 y., 72 procedures performed, of LAA occluder implantation for patients with high thromboembolic and hemorrhagic risk (mean age 68±7,4 y. o., 48 females, 24 males, mean rate by CHA2DS2VASc 4,82±1,48 points), of those 3 underwent single-moment cryoballoon isolation of the PV ostia without electrical isolation of LAA. The parameters of the intervention were assessed, and prevalence of intra-operation complications in AF patients that included single-moment catheter cryoballoon isolation of PV ostia and implantation of LAA occluding device, in comparison with isolated LAA occluder implantation.Results. Occluding device implantation was successful in 100% cases. Periprocedural efficacy of PV ostia isolation was 100%. In both groups, intraoperational complications were absent. Mean heparin time and dosage of contrast in the hybrid intervention group were higher: 94,3±6,8 min vs 59,7±19,95 min (p<0,05), 196,8±20,82 mL vs 124,6±30,24 mL (p<0,05), respectively.Conclusion. Performing of the hybrid intervention that includes single-moment catheter isolation of PV ostia and implantation of the occluding device into LAA increases mean procedure duration and contrast load in comparison to isolated LAA occluder implantation, with no operational risk increase.